2017
DOI: 10.1080/02713683.2016.1276196
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Central Serous Chorioretinopathy: Multivariate Approach in a Case-Control Study

Abstract: It is important to take into account the various risk factors for CSR, so as to define vulnerable groups and to shed light into the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
5
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 36 publications
2
88
5
16
Order By: Relevance
“…; Chatziralli et al. ), we did not find any evidence to support this. Critical evaluation of the available literature revealed that type A behavioural characteristics were mainly assessed using behavioural outcome measures (i.e.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…; Chatziralli et al. ), we did not find any evidence to support this. Critical evaluation of the available literature revealed that type A behavioural characteristics were mainly assessed using behavioural outcome measures (i.e.…”
Section: Discussioncontrasting
confidence: 86%
“…; Chatziralli et al. ). On the level of conduct, patients did not report more psychological morbidity in the form of apathy or irritability.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Spaide et al asserted that nicotine exposure may cause nitric oxide-induced abnormalities of choroidal vessels and induce CSC 11 17 28. Myopia has been reported to be a protective factor17 29 and hyperopia a risk factor 17. Our study revealed that one dioptre hyperopic change in spherical equivalent refractive error increases, and one dioptre myopic change decreases, the odds of being a patient with CSC by 24.6%.…”
Section: Discussionmentioning
confidence: 49%